Beyond Blood Glucose and Blood Pressure Control in Type 2 Diabetes: Alternative Management Strategies to Prevent the Development and Progression of CKD - Wendy L. Wright; Scott Urquhart; Stephen Brunton (SAGE Publishing, 2023)
Chronic kidney disease associated with Type 2 diabetes is linked to significant increase in morbidity, reduced quality of life, and early death. Current guidelines recommend targets for the management of hyperglycemia, hypertension, and dyslipidemia but there remains a residual risk of chronic kidney disease progression and adverse cardiovascular outcomes in patients with Type 2 diabetes. The 2022 consensus report from the American Diabetes Association and Kidney Disease: Improving Global Outcomes support the use of sodium-glucose co-transporter 2 inhibitors and nonsteroidal mineralocorticoid receptor antagonists to improve kidney and cardiovascular outcomes. Coordination between those working in the primary care setting and those in endocrinology and nephrology clinics may optimize the prevention of chronic kidney disease progression in patients with Type 2 diabetes. Nurse practitioners, physician assistants, and primary care physicians play an important role in making timely patient referrals to kidney specialists. This article explores the use of novel therapies capable of reducing the risk of cardiovascular disease and chronic kidney disease progression beyond what can be achieved with control of blood glucose, blood pressure, and lipid levels. It also discusses the importance of monitoring at-risk patients to facilitate early diagnosis and initiation of effective kidney-protective therapy. SAGE-Journals-Accessible-Video-Player 10.1177/21501319231153599.M1 sj-vid-1-jpc-10.1177_21501319231153599 Figure 1. ( Press play for video abstract ) Multidisciplinary care model for identification of patients with T2D and CKD at high risk of CV and kidney events. a Discontinuation of ACE/ARB for minimal increases in serum of creatinine in absence of volume depletion should be avoided. Adapted from the American Diabetes Association Standards of Medical Care in Diabetes 2022 5 and Addendum. 11. Chronic Kidney Disease and Risk Management: Standards of Medical Care in Diabetes-2022. 6 Abbreviations: ACE, angiotensin-converting enzyme; ARB, angiotensin receptor blocker; BP, blood pressure; CKD, chronic kidney disease; CV, cardiovascular; eGFR, estimated glomerular filtration rate; MRA, mineralocorticoid receptor antagonist; RAAS, renin-angiotensin-aldosterone system; SGLT2, sodium-glucose co-transporter 2; T2D, Type 2 diabetes, UACR, urine albumin:creatinine ratio.